The American Family in 1990: Growing Diversity and Inequality - Lynne Casper; Sara McLanahan (Luxembourg Income Study (LIS), 1994)
This paper examines four demographic trends which underlie the changes in the American family. Family diversity and its implications for the economic well-being of American women is also examined.
Keywords: 330